A Decent Place To Live From Columbia Point to Harbor Point-A Community History - Roessner, Jane (Northeastern University Press, 2019)
When Boston's Columbia Point housing project was built in the early 1950s on the isolated edge of Dorchester Bay, it was hailed as a noble government experiment to provide temporary housing for working-class families who had fallen on hard times. By the mid-1970s, the model community had disintegrated and become a symbol of failure, decay, crime, and danger. Today, Columbia Point has been redeveloped as Harbor Point, a privately owned and managed mixed-income, racially integrated complex that stands handsomely alongside its institutional neighbors, the John F. Kennedy Library, the Massachusetts Archives, and the University of Massachusetts at Boston. A Decent Place to Live chronicles the rise, fall, and rebirth of Columbia Point through the voices of those who struggled to make a life there and who battled to rebuild their community. A fascinating story of people, conflict, continuity, and change, the work captures the rich yet troubled heritage of Columbia Point and celebrates the aspirations and tenacity of its residents. It reclaims a neglected piece of Boston's history and offers important lessons for urban planners and policy makers nationwide. Originally published by Northeastern University Press in 2000. With a new foreword by Karilyn Crockett.